2014
DOI: 10.1590/s1519-99402014000100015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crude glycerol on in-vitro ruminal fermentation kinetics

Abstract: SUMMARYThe interest in using crude glycerol in animal feeding has reemerged due to its increasing availability and favorable price resulting from the expansion of biofuel industry. The objective of the present study was to evaluate the effects of substituting corn for crude glycerol at different levels in the diet on ruminal fermentation using in-vitro true digestibility parameters. The experimental treatments consisted of substituting corn for liquid crude glycerol (0; 4; 8 and 12%) in dry matter basis. Diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Similar results for fractions B and C were obtained by Oliveira Filho et al (2015) when evaluating the inclusion of CG up to 90 g per kg DM of sorghum silage. Peripolli et al (2014), however, did not observe differences in ruminal degradation parameters of NDF when evaluating the substitution of corn by glycerol at levels up to 12 %. The non-significant effect (P>0.05) of CG levels on DM intake and a similar proportion of nutritional compounds in the diets can explain the non-significant (P>0.05) effect of CG levels on OM, NDFap, CP, NFC, EE, and TDN intake.…”
Section: Discussionmentioning
confidence: 59%
“…Similar results for fractions B and C were obtained by Oliveira Filho et al (2015) when evaluating the inclusion of CG up to 90 g per kg DM of sorghum silage. Peripolli et al (2014), however, did not observe differences in ruminal degradation parameters of NDF when evaluating the substitution of corn by glycerol at levels up to 12 %. The non-significant effect (P>0.05) of CG levels on DM intake and a similar proportion of nutritional compounds in the diets can explain the non-significant (P>0.05) effect of CG levels on OM, NDFap, CP, NFC, EE, and TDN intake.…”
Section: Discussionmentioning
confidence: 59%
“…In the negative control, offering only mineral supplementation, the mean value of the experimental periods was below 5 mg of N-NH 3 /dL of ruminal liquid, below the critical value for the synthesis of microbial protein in animals on forage-based diets (LENG, 1990;DETMANN et al, 2009). In previous studies, Abo El-nor et al (2010), Peripolli et al (2014), and Botini et al (2015) evaluated the replacement of corn by increasing levels of crude glycerin and observed no effects on ruminal NH 3 concentrations. Serum blood glucose was not affected by protein-energy supplementation or the level of crude glycerin inclusion in supplements.…”
Section: Resultsmentioning
confidence: 94%
“…Previous study evaluating degradation of OM and NDF reported no differences, when crude glycerin was added at up to 12% in diets for lambs in vitro (Peripolli et al, 2014). However, even at low concentration crude glycerin seems affect in situ ruminal degradation parameters of steers.…”
Section: In Situ Ruminal Degradabilitymentioning
confidence: 82%